Evaluation of Thyroid Nodules in Children and Adolescents: Multicenter Study in Turkey - Kaplan, Emel Hatun Aytac; Cakir, Aydilek Dagdeviren; Esen, Ihsan; Akbas, Emine Demet; Bitkin, Eda Celebi; Akyurek, Nesibe; Keskin, Mehmet (Galenos Publ House, 2021)
Introduction: Ultrasonography and fine needle aspiration biopsy are reliable diagnostic methods used to predict malignancy in thyroid nodules. They are useful in identifying patients for therapy or preventing unnecessary surgery. Materials and Methods: The aim of this study was to compare clinical and ultrasonographic findings with fine needle aspiration biopsy and histopathological examination results in children with thyroid nodules. Retrospective study. This multicentre study included pediatric patients with thyroid nodules, followed up between July 2002 and November 2019 in nine Turkish Pediatric Endocrinology Units. Clinical, ultrasonographic, cytological and histopathological findings (malignant or benign) were analyzed retrospectively. Fine needle aspiration biopsy findings were classified according to American Thyroid Association criteria. Results: A total of 203 children were included, of whom 82.3% (n=167) were female. Mean +/- standard deviation age was 14.06 +/- 2.26 (range 3.7-19) years. Cytological diagnoses were: non-diagnostic or unsatisfactory 1.9%; benign 59.6%; atypia or follicular lesion of undetermined significance, suspicious for follicular neoplasm in 2.4%; suspicious for malignancy 12.8%; and malignant in 1.9%. Surgery was performed in 59 (29.1%) patients. In total 33 (16.3%) patients were diagnosed with malignancy. In patients with benign fine needle aspiration biopsy results, malignancy was detected in 17.6% when they underwent surgery. Malignancy was present in 44.4% of the patients with cytologically determined atypia or follicular lesion of undetermined significance. The diagnostic accuracy of fine needle aspiration biopsy was 79%. Conclusion: This study is first multicentre study investigating thyroid nodules in children and adolescents in Turkey. In this population fine needle aspiration biopsy has an important role in diagnosis, but ultrasonographic features of nodule should also be taken into consideration. Atypia or follicular lesion of undetermined significance may be of greater clinical significance than has previously been reported.
Çocuk ve Adolesanlarda Tiroid Nodüllerinin Değerlendirilmesi: Türkiyede Çok Merkezli Çalışma
Keywords: Childhood; fine needle aspiration biopsy; thyroid; ultrasonography